Evaluation of the Effect of Dapagliflozin on CRP Levels in Type 2 Diabetes Patients - Yosef, Boshra; Kaddar, Nisrin; Boubou, Arige (Jordan Journal of Pharmaceutical Sciences, 2023)
Type 2 diabetes mellitus (T2DM) is an increasingly prevalent chronic disease that associates with an increased risk of micro-and macrovascular complications. There is persuasive evidence that dapagliflozin may reduce chronic inflammation besides its glucose-lowering effect, which in term prevents the development of the disease and its complications. Therefore, this study aims to evaluate the effects of dapagliflozin on the inflammatory marker C-reactive protein (CRP) levels in T2DM patients. Patients with T2DM were randomly assigned into two groups, group 1 (n=52) receiving a daily dose of dapagliflozin as an add-on therapy with oral antihyperglycemic agents, and group 2 (control, n=60) who received oral antihyperglycemic agents (Metformin, Sulfonylureas, Thiazolidinediones, and Gliptins). After six months, our results showed a significant change in CRP levels from baseline after receiving dapagliflozin compared to the control. Although the reduction level of CRP was statically significant with both 5 mg and 10 mg doses, it was higher with the latter one. In addition, the reduction in CRP levels was statistically significant in both controlled and uncontrolled, but more important in uncontrolled disease. An insignificant positive correlation was seen between HbA1c and CRP on admission (r: 0.21, p: 0.1) and during the follow-up period, at 3 months (r: 0.10, p: 0.4) and 6 months (r: 0.08, p: 0.5). Our study showed that dapagliflozin has a beneficial effect on inflammation by reducing CRP levels CRP in patients with T2DM.